Vascular hamartoma in horse limbs: presentation, diagnosis, and treatment of two case studies - Apolonio, Emanuel Vitor Pereira [UNESP]; Gobbo, Laís Loiola [UNESP]; Woiblet, Nathalia Gouveia [UNESP]; Dinau, Fernando Carmona [UNESP]; Pyles, Mateus Siqueira; Ferrari, Lorena Cardozo [UNESP]; de Moura Alonso, Juliana; Alves, Ana Liz Garcia [UNESP] (Springer Nature, 2025)
Vascular hamartoma is an abnormal development of endothelial tissue that rarely affects horses. Histopathological examination remains the gold standard for definitive diagnosis, yet the presence of abnormal vascular structures must be carefully differentiated from other vascular anomalies and neoplasms. This report describes two cases of vascular proliferation affecting the skin on the lateral side over the left tarsus and the dorsolateral region over the fetlock joint of two fillies. The clinical history, presentation, and radiographic and sonographic findings in both patients suggested a neoplasm of unknown origin. Surgical excision of the mass was successfully performed in both patients. In one patient, a second surgery was performed six months after the first surgery because of the recurrence of the mass. Histopathological examination revealed a disorganized proliferation of well-differentiated, tortuous, and varied-sized blood vessels hemmed in myxoid tissue with abundant fibrocollagenous bands. Immunohistochemical examination of the endothelium markers factor VIII and ERG revealed positive staining of the mass samples in both cases, confirming their vascular origin. The combination of these markers was effective, providing a reliable option for differentiating vascular proliferation in horses. To the best of the author’s knowledge, this is the first report applying the ERG endothelial marker to horse vascular malformations.
Keywords: Equine surgery; ERG; Factor VIII; Immunohistochemistry